Barley and Wheat Share the Same Gene Controlling the Short Basic Vegetative Period - Rui-hua LÜ; Yan-hao XU; Rodger Boyd; Xiao-qi ZHANG; Sue Broughton; Michael Jones; Cheng-dao LI; Yao-feng CHEN (Journal of Integrative Agriculture)
Basic vegetative period (BVP) is an important trait for determining flowering time and adaptation to variable environments. A short BVP barley mutant is about 30 d shorter than its wild type. Genetic analysis using 557 F2 individuals revealed that the short BVP is governed by a single recessive gene (BVP-1) and was further validated in 2 090 F3 individuals. The BVP-1 gene was first mapped to barley chromosome 1H using SSR markers. Comparative genomic analysis demonstrated that the chromosome region of BVP-1 is syntenic to rice chromosome 5 and Brachypodium chromosome 2. Barley ESTs/genes were identified after comparison with candidate genes in rice and Brachypodium; seven new gene-specific markers were developed and mapped in the mapping populations. The BVP-1 gene co-segregated with the Mot1 and Ftsh4 genes and was flanked by the gene-specific markers AK252360 (0.2 cM) and CA608558 (0.5 cM). Further analysis demonstrated that barley and wheat share the same short BVP gene controlling early flowering.